The relationship between serum and sputum levels of azithromycin and clinical endpoints in patients with bronchiectasis using azithromycin maintenance treatment - Altenburg, Josje; Wilms, Erik B; Boersma, Wim G (Archives of Pharmacy and Pharmaceutical Sciences, 2019)
Background: Azithromycin (AZM) is a macrolide antibiotic with distinct pharmacokinetic properties and is increasingly used as maintenance treatment in patients with bronchiectasis in order to reduce infectious exacerbations and improve pulmonary symptoms. The exact mechanism of action is not known and the relation between azithromycin dose level, local and systemic drug levels and clinical effect however, has not been extensively studied yet. Objectives: To explore the relation between AZM serum and sputum concentrations, clinical effect parameters and side effects. Methods: Azithromycin concentrations were measured in serum and sputum samples of bronchiectasis patients receiving one year of AZM treatment (250mg OD) enrolled in the Bronchiectasis and Azithromycin Treatment (BAT) trial, a double blind, randomised placebo-controlled trial. Results were correlated with data on AZM dose level, exacerbation frequency, lung function (forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC), quality of life and symptoms collected within the same year. Results: 83 sputum samples from 31 patients and 151 serum samples from 43 patients were available for analysis. Mean AZM dose-level ranged from 18.8 to 39.8 mg/kg body weight/ week, generating mean AZM concentrations of 7.57 mg/L (SD 9.49) in sputum and 0.11 mg/L (SD 0.085) in serum. No correlation was found between side effects and AZM dose level, sputum- or serum concentrations. Significant correlation was found between AZM sputum concentration and CRP-level (r= -0.6). Conclusion: High and stable AZM sputum levels were reached during long term treatment, as opposed to low AZM levels in serum. Apart from CRP-levels to AZM sputum concentration, no other outcome parameter showed significant correlation to AZM serum- or sputum levels. AZM dose- or exposure levels were not predictive for the occurrence of side effects.